Proceedings of the Conference on Recent Advances in Rock Engineering (RARE 2016) 2016
DOI: 10.2991/rare-16.2016.59
|View full text |Cite
|
Sign up to set email alerts
|

Landslide in fractured and stratified rocks - A case from Aizawl, Mizoram, India

Abstract: Abstract-Stratified rock cut slopes for e.g. shale-sandstonesiltstone layers are a common occurrence in some part of the Himalayas. These rocks are highly jointed and bears low strength to sustain significant engineering load. A similar geological condition exists in the north eastern Himalayas (Aizawl, Mizoram) where such rocks have been exposed along cut slopes. The area receives heavy rainfall during the monsoonal months and the presence of clay make these rocks highly susceptible to intense weathering. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Zhang et al 18 and Elkamhawy et al 19 found that during rainstorm, the stability of the slope decreases, the rainfall infiltration leads to the decrease of soil shear strength, through monitoring the positive pore water pressure and horizontal earth pressure of soil under rainfall conditions. 20,21 Besides, Huang et al 22 performed a numerical simulation to calculate the stability coefficient of the Three Gorges Project affected by reservoir water level fluctuations and rainstorms. The analysis was based on saturated–unsaturated seepage theory and finite element analysis, and the trend of the safety factor and seepage characteristics of the slope was analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 18 and Elkamhawy et al 19 found that during rainstorm, the stability of the slope decreases, the rainfall infiltration leads to the decrease of soil shear strength, through monitoring the positive pore water pressure and horizontal earth pressure of soil under rainfall conditions. 20,21 Besides, Huang et al 22 performed a numerical simulation to calculate the stability coefficient of the Three Gorges Project affected by reservoir water level fluctuations and rainstorms. The analysis was based on saturated–unsaturated seepage theory and finite element analysis, and the trend of the safety factor and seepage characteristics of the slope was analyzed.…”
Section: Introductionmentioning
confidence: 99%